2012
DOI: 10.1016/j.cell.2012.04.030
|View full text |Cite
|
Sign up to set email alerts
|

The Intra-S Phase Checkpoint Targets Dna2 to Prevent Stalled Replication Forks from Reversing

Abstract: When replication forks stall at damaged bases or upon nucleotide depletion, the intra-S phase checkpoint ensures they are stabilized and can restart. In intra-S checkpoint-deficient budding yeast, stalling forks collapse, and ∼10% form pathogenic chicken foot structures, contributing to incomplete replication and cell death (Lopes et al., 2001; Sogo et al., 2002; Tercero and Diffley, 2001). Using fission yeast, we report that the Cds1(Chk2) effector kinase targets Dna2 on S220 to regulate, both in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 44 publications
(62 reference statements)
11
161
1
Order By: Relevance
“…7). These restart events may entail nucleolytic degradation rather than branch migration of the reversed forks (12), in agreement with the nucleolytic processing of reversed forks previously reported in yeast (38,39). Regardless of their source, postreplicative ssDNA gaps can certainly contribute to explain the observed accumulation of RAD51 in PARG-depleted cells.…”
Section: Discussionsupporting
confidence: 70%
“…7). These restart events may entail nucleolytic degradation rather than branch migration of the reversed forks (12), in agreement with the nucleolytic processing of reversed forks previously reported in yeast (38,39). Regardless of their source, postreplicative ssDNA gaps can certainly contribute to explain the observed accumulation of RAD51 in PARG-depleted cells.…”
Section: Discussionsupporting
confidence: 70%
“…In general, the cells require DNA2 for repression of replicative stress. DNA2 can trigger proper intra-S-phase checkpoints, 49 prevent replication fork reversal, 50 and restart replication when forks have already undergone reversal. 51 However, in response to ICL-inducing agents, DNA2 contributes to over-resection of DNA due to an imbalanced hyperactivation of its nuclease activity in response to loss of FancD2 and/or to impairment of the replication fork stabilizer BOD1L.…”
Section: Ganetespib Carboplatin Combinationmentioning
confidence: 99%
“…As described under "Materials and Methods," G 1 -arrested cells were released into media containing 20 M CPT or 0.033% MMS. MMS is known to activate the intra-S-phase checkpoint by interfering with progression of replication fork progression (14,47,48), whereas CTP fails to do so (42). DNA was purified from the samples taken at regular (20 or 30 min) intervals after release.…”
Section: Unimpeded S-phase Progression Is Observed In Dna2⌬405n Follomentioning
confidence: 99%
“…In Saccharomyces cerevisiae, the endonuclease activity of Dna2 is essential for viability (3,4), whereas its helicase activity is dispensable under some growth conditions (12,13). Recently, it was shown that Dna2 contributes to the protection of stalled replication forks by inhibiting reversion of replication forks in a manner dependent on the intra-S-phase checkpoint in Schizosaccharomyces pombe (14). The enzymatic properties of Dna2 endonuclease are suited to remove flaps generated from 5Ј-ends of Okazaki fragments by DNA displacement activity of DNA polymerase (pol) ␦ (13,15).…”
mentioning
confidence: 99%